Biological Control Mechanisms of Non-Saccharomyces Yeasts against Filamentous Fungal Pathogens within Rosaceae Family - Giseli Cristina Da Costa Arruda; Mónika Kovács; Andrea Pomázi (International Journal of Agronomy)
Pathogenic fungi can cause significant annual losses in the quality and quantity of fruits belonging to Rosaceae family during pre- and postharvest. Synthetic fungicides are considered the main method for controlling diseases in food crops; however, they pose a great risk to human health and to the environment. As a result, biological control methods, which are based on living microorganisms to reduce the population or to inhibit the growth of pathogens, have arisen as a safe alternative. In this review, we highlight the principal mechanisms (e.g., nutrition and space competition, mycoparasitism, induced resistance and growth enhancement, production of volatile organic compounds, and antibiosis) utilized by the most frequently reported non-Saccharomyces biocontrol agents (BCAs) yeasts: Meyerozyma guilliermondii, Pichia membranifaciens, Wickerhamomyces anomalus, Metschnikowia pulcherrima, Hanseniaspora uvarum, and Aureobasidium pullulans, against the common pathogenic fungi found within Rosaceae family: Penicillium expansum, Botrytis cinerea, and Monilinia spp. Understanding BCAs’ importance and mode of action is a necessary step in order to reduce the detrimental effect of spoilage fungi in the agriculture and food industry, by achieving a more sustainable and safer control of them.